Debt relief and civil war - Tony Addison; S. Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Of the 41 HIPCs, 11 are classified by the IMF and World Bank as conflict-affected. Can debt relief reduce the level of violent conflict in these countries? By providing additional resources to finance broad-based public spending, debt relief could help to redress the grievances that contribute to conflict. It could also reduce the ability of those motivated by greed to recruit followers, since the incomes, and therefore the grievances of followers, will fall if they benefit from broad-based public spending. But four things can go wrong with the use of debt relief in this way. First, the war party may prevail over the peace party in government, especially if the war party profits directly from conflict. Second, the fiscal system may be so institutionally weak that it cannot achieve the promised fiscal transfer even if the peace party prevails. Third, the rebel leaders may capture most of the fiscal transfer, leaving the grievances of their followers to ferment into further conflict. Fourth, a fiscal transfer that could have prevented conflict may be insufficient to stop a war once it begins, since rebels will seek out war-related income (and external finance) that may substantially exceed any promised post-war fiscal transfer. Hence, other forms of international action will be necessary alongside debt relief to end conflict.
Keywords: C72; F34; F35; O10; O55; 330; debt relief; conflict; fiscal policy; sub-Saharan Africa; Schuldenerlass; Bürgerkrieg; Theorie